CHILDHOOD MOOD DISORDERS DURING PANDEMIC; LEARNING MANAGEMENT BASED ON SELF DISCIPLINE - Akmal Mundiri; Chodijatus Sholehah (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
This paper describes the management of early childhood mood in the midst of the COVID-19 pandemic through qualitative research approaches and types of case studies. Covid’s-19 pandemic that hit the world has changed most of human activities. This pandemic anables everyone to do their own work by staying at home, studying at home and working at home. It was requested that the government had appealed. This research aims to learn how to regulate early childhood moods so that they can be disciplined in the midst of this pandemic. There are several methods that can be used, use the exemplary method, habitation, and discuss individuals. Besides that, there are other things that can also be done, such a giving awards to children who have met the specified discipline standards, for example, providing additional play time. And give punishment the sentence consist of no award received, not with punches, screams or twists.